[tex]
\it (AB) : \dfrac{y-y_A}{y_B-y_A} = \dfrac{x-x_A}{x_B-x_A}[/tex]
[tex]\it \dfrac{y-2}{3-2}=\dfrac{x-2}{3-2} \Longrightarrow y-2=x-2|_{+2} \Longrightarrow y= x\ ( prima \ \ bisectoare)[/tex]
[tex]\it (AC) : \dfrac{y-y_A}{y_C-y_A} = \dfrac{x-x_A}{x_C-x_A} [/tex]
[tex]\it \dfrac{y-2}{-4-2}=\dfrac{x-2}{-2-2} \Longrightarrow \dfrac{y-2}{-6}=\dfrac{x-2}{-4} \Longrightarrow \dfrac{y-2}{6}=\dfrac{x-2}{4} \Longrightarrow
\\\; \\ \\\;\\
\Longrightarrow 2y-4=3x-6 \Longrightarrow 2y = 3x-2\Longrightarrow y=\dfrac{3}{2}x -1\ \ .[/tex]